LITERATURE REVIEW OF THE PHARMACOLOGICAL ACTIVITIES OF THE EUPHORBIACEAE FAMILY PLANTS - Maulana Isman Naki; Abulkhair Abdullah; Elis Susilawati (Jurnal Farmasi Sains dan Praktis, 2023)
Euphorbiaceae family plants are spread in Indonesia and empirically, have been used for a long time as medicine. This article review aims to discuss the pharmacological activities of several plants from the Euphorbiaceae family. This research was conducted by conducting a literature review limited to research in the form of scientific articles. The scientific article in question results from research reviewed and published in Indonesian and English. The steps in the search are divided into several stages, starting from identification, screening, eligibility, and data grouping. The articles used in this article review were obtained by searching the internet from online data search media/search engines such as Google/Google Scholar and journal provider sites such as PubMed, NCBI, and SINTA with the keywords "Euphorbiaceae plants," "Ethnopharmacology, "Ethnobotany and Ethnopharmacy," "Plant Activity and Effectiveness," "Euphorbiaceae family activity," and "Pharmacological activity of Euphorbiaceae. After determining the keywords, the next step is filtering multiple data or duplications and filtering the article's title, abstract, and keywords so that data can be determined to be used or not for the following review.This study is a literature review based on several national or international scientific articles about the pharmacological activity of Euphorbiaceae plants. The literature study found that some plants from the Euphorbiaceae family have pharmacological activities, and the most dominant are antimicrobial, antioxidant, and anti-inflammatory. Moreover, many other activities include analgesic, antipyretic, antithrombotic, anti-hypercholesterolemia, antihyperglycemic, antihistamine, diuretic, and antiseptic.